Adaptive Morphing and Coping with Social Threat in Autism: An Autistic Perspective - Lawson, Wenn B. (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
This paper highlights the role of terminology, such as camouflage and masking, commonly used in autism research. The author suggests researchers question assumptions around language commonly used to check it is fully representative of the autistic position. Being autistic often means being very literal. This literality means it is very important for researchers – particularly non-autistic researchers – to design research questions in a way that will gather accurate information often underlying autistic understanding. Words are powerful tools and lead to beliefs and positions held. Adaptive morphing in autism (currently referred to as camouflage or masking) infers a response, not of deceit, but one that is biological and not necessarily chosen. The author of this paper suggests masking, as a choice to deceive, is quite different from adaptive morphing for safety.